Recrutamento de corais recifais no Banco dos Abrolhos, Brasil - Alvarenga, Márcia Fernandes (2004)
Recruitment pattem of different families of scleractinian corais and milleporids were studied at the inner reefs of the Abrolhos Bank, to improve our understanding of processes of population formation and maintenance. The identity and abundance of recruits, coral cover, and sediment deposition, among other variables, were investigated at six reefs. We recovered 140 plates with a total of 2,532 recruits identified. Brooders families had higher recruitment rates than broadcasters. Recruits were dominated by Poritidae (29%), followed by Milleporidae (24%) and Faviidae (19%). We did not observe recruits of Mussidae, family composed mainly by broadcaster species with relatively high adult cover at the studied reefs. There was a significant correlation between the recruitment of Milleporidae, Faviidae nd Astrocenidae and adult's abundance of these taxa or one of its species. We suggest such correlation may be associated with larval attraction processes and not with local recruitment. No correlation was found between recruitment rates and sediment deposition.